Association of proinflammatory molecules with apoptotic markers and survival in critically ill multiple organ dysfunction patients - Papathanassoglou, Elizabeth; Moynihan, Jan; Dafni, Ourania; Mantzoros, Christos S.; Ackerman, Michael John (My University, 2003)
Recent evidence supports the involvement of apoptosis in multiple organ dysfunction (MODS). The authors examined the hypothesis that nitric oxide (NO), interleukin (IL)-6, tumor necrosis factor (TNF)-α, and cortisol correlate with Fas and Fas ligand (FasL) expression on peripheral blood mononuclear cells and that Fas and FasL, therefore, mediate their association with MODS severity. Thirty-five critically ill adult MODS patients were followed for up to 14 days and were compared to non-MODS matched controls. Fas, FasL, nitrate, cortisol, and IL-6 were elevated in MODS patients (P < 0.05). Nitrate and cortisol correlated with Fas expression (P < 0.05). All factors studied, except for TNF-α, correlated with MODS severity (P< 0.05); however, by multivariate analyses, Fas and FasL were independently associated with severity and survival (P < 0.05). The inflammatory molecules studied may mediate the association of apoptotic constituents with MODS severity and survival only in part.
Keywords: MODS; Apoptosis; Fas; Cytokines; Nitric oxide; Cortisol; Interleukin-6; Tumor necrosis factor-α